2015
DOI: 10.4081/ijas.2015.3533
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Energy Digestibility and Prediction of Digestible and Metabolisable Energy in Sunflower Seed Meal Fed to Growing Pigs

Abstract: The experiment was conducted to determine the chemical composition, digestible energy (DE), metabolisable energy (ME) and the apparent total tract digestibility (ATTD) in sunflower seed meal (SFSM) and to develop reasonable prediction equations for estimating energy digestibility based on chemical composition of these meals for growing pigs. Ten SFSMs were collected and 66 crossbred barrows (initial body weight=36.43±5.25 kg) were randomly allocated to one of eleven diets. The basal diet was based on corn and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 22 publications
4
11
1
Order By: Relevance
“…Noblet and van Milgen () reported that energetic efficiency ofDF (60%) is lower than that of lipids (90%) and starch (82%). Concentrations of DE and ME in SFM were within the range of values previously reported by Liu et al (). The lower DE concentration in HPB diet compared with LPB diet may be due to its higher fibre concentration and lower digestibility of fibre which contributed to the lower ATTD of GE in HPB diet.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Noblet and van Milgen () reported that energetic efficiency ofDF (60%) is lower than that of lipids (90%) and starch (82%). Concentrations of DE and ME in SFM were within the range of values previously reported by Liu et al (). The lower DE concentration in HPB diet compared with LPB diet may be due to its higher fibre concentration and lower digestibility of fibre which contributed to the lower ATTD of GE in HPB diet.…”
Section: Discussionsupporting
confidence: 88%
“…The decreased AID and SID of Met as dietary NDF level increasing from 12% to 16% may be due to the ‘net synthesis’ for Met in the large intestine of pigs when diets are supplemented with DF (Wang et al, ). The increased ileal digestibility of some AA in diet with or without SFM as dietary NDF increased from 12% to 16% was mainly depended on chemical composition and AA composition of WB and SFM (Liu et al, ; Rojas, Vinyeta, & Stein, ). The primary reason for the decreased SID of AA as dietary NDF increasing from 12% to 16% may be due to the specific endogenous losses induced by high fibre and so for the calculation values of SID.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diets included a corn-soybean meal based basal diet and 5 test diets containing 29.25% FFRB, 29.25% CGM, 24.38% CGF, 19.50% PNM, or 29.25% SFM added at the expense of corn and soybean meal ( Table 2 ). The inclusion levels of the five ingredients used in this experiment were based on inclusion levels used in previous experiments [ 1 , 2 , 4 , 5 ].…”
Section: Methodsmentioning
confidence: 99%
“…Several research projects have been conducted to evaluate the nutrient content and the digestibility of energy of FFRB [ 1 ], CGM and CGF [ 2 , 3 ], PNM [ 4 ], and SFM [ 5 , 6 ]. However, there is a lack of information about the measured net energy (NE) content of these ingredients and the NE values of these ingredients that are available are based on prediction equations using digestible energy (DE), metabolizable energy (ME) or digestible nutrients contents [ 7 ].…”
Section: Introductionmentioning
confidence: 99%